ANALISIS PENANAMAN NILAI TOLERANSI DAN KEBHINEKAAN GLOBAL MELALUI MATERI KERAGAMAN SOSIAL BUDAYA PADA PEMBELAJARAN IPS KELAS VI SEKOLAH DASAR - Lailatul Rachmawaty; Wilda A’malina Zatinuha; Zahra Najma Audiva; Sania Br Tampubolon; Priyono Tri Febrianto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Indonesia’s diversity in ethnicity, culture, and religion represents both a valuable asset and a potential source of social conflict if not properly managed through tolerance. This study aims to examine how social and cultural diversity materials can foster tolerance and global diversity values among sixth-grade elementary students. The research employs a Systematic Literature Review (SLR) method by analyzing scientific articles published between 2021 and 2026. Out of 100 initial articles, 16 relevant studies were selected for in-depth analysis. The findings reveal that integrating multicultural values into social studies learning effectively enhances students’ tolerance. All reviewed studies confirm that contextual and experience-based approaches help transform students’ understanding of differences into real-life behavior. Learning that connects content with students’ social realities is more meaningful in shaping mutual respect. Therefore, diversity-related materials in social studies play a crucial role as a foundation for developing inclusive character and social skills, enabling students to navigate diversity in the future.